2014
DOI: 10.1037/a0037178
|View full text |Cite
|
Sign up to set email alerts
|

Does adolescents’ religiousness moderate links between harsh parenting and adolescent substance use?

Abstract: Extant literature suggests that religiousness is inversely related to adolescent substance use; yet, no systematic investigation has examined whether religiousness may be a protective factor against substance use in the presence of risk factors. We examined whether religiousness moderates the links between parents’ psychological and physical aggression and adolescent substance use directly and indirectly through adolescent self-control. The sample comprised adolescents (N = 220, 45% female) and their primary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 66 publications
(91 reference statements)
1
21
0
Order By: Relevance
“…Specifically, Lamis, Malone, Lansford, and Lochman () found that harsh parental discipline was associated with adolescent alcohol‐use onset, and Zucker, Donovan, Masten, Mattson, and Moss () found that harsh and inconsistent parenting during early adolescence significantly predicted adolescent involvement in both tobacco and alcohol use, especially among adolescents 16 years and older. Similarly, Kim‐Spoon, Farley, Holmes, and Longo () found that adolescents were more likely to engage in substance use when raised by parents who used psychological and physical aggression. Other studies suggest that adolescents raised by harsh parents are at greater risk for involvement in risky behaviors than those youth who experience a more supportive style of parenting (Adalbjarnardottir & Hafsteinsson, ).…”
Section: Harsh Parenting and Adolescent Risky Behaviormentioning
confidence: 92%
“…Specifically, Lamis, Malone, Lansford, and Lochman () found that harsh parental discipline was associated with adolescent alcohol‐use onset, and Zucker, Donovan, Masten, Mattson, and Moss () found that harsh and inconsistent parenting during early adolescence significantly predicted adolescent involvement in both tobacco and alcohol use, especially among adolescents 16 years and older. Similarly, Kim‐Spoon, Farley, Holmes, and Longo () found that adolescents were more likely to engage in substance use when raised by parents who used psychological and physical aggression. Other studies suggest that adolescents raised by harsh parents are at greater risk for involvement in risky behaviors than those youth who experience a more supportive style of parenting (Adalbjarnardottir & Hafsteinsson, ).…”
Section: Harsh Parenting and Adolescent Risky Behaviormentioning
confidence: 92%
“…Conger and colleagues (1991) found that marital conflict was directly related to adolescent drinking, which may be a coping response to family stress. In terms of parenting, it has been found that harsh parenting practices were linked to alcohol use during adolescence (Kim-Spoon, Farley, Holmes, & Longo, 2014). Moreover, coercive parental control (Aquilino & Supple, 2001) and father harsh parenting (Diggs et al, 2017) in the early adolescent years has been associated with increased substance use in later adolescence and emerging adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Parents are prominent socialization agents whose substance use perceptions, attitudes, and behaviors influence their adolescents’ substance use behaviors directly or indirectly (Becker, ; Newcomb, Huba, & Bentler, ). Parents with a history of substance use may demonstrate deficits in parenting behaviors (Darling & Steinberg, ) which may pose distal socialization risks for adolescent substance use via adolescents’ social selection and peer affiliation (Jessor, ; Kim‐Spoon, Farley, Holmes, & Longo, ). Adolescents seek out peers who possess substance use attitudes and behaviors not only similar to their parents’ current substance use behaviors (Ennett et al., ), but similar to their parents’ former substance use behaviors as well (Kerr, Tiberio, & Capaldi, ).…”
Section: Associations Among Parent Peer and Adolescent Substance Usementioning
confidence: 99%
“…It is expected that religious social support may exert buffering effects against social risks for substance use behaviors during adolescence, given the protective role of religiousness in promoting positive adolescent adjustment in the presence of family (Kim‐Spoon et al., ; Wills, Yaeger, & Sandy, ) and peer risk factors for adolescent substance use (Allen, Chango, Szwedo, Schad, & Marston, ). For example, a cross‐sectional study of the interactive effects of religiousness and harsh parenting on adolescent substance use demonstrated buffering effects of religiousness (Kim‐Spoon et al., ). Specifically, adolescents subjected to harsh parenting were more likely to use substances (cigarettes, alcohol, and marijuana) at low but not high levels of religiousness (using a composite involving organizational religiousness, personal religiousness, and religious social support).…”
Section: Associations Among Parent Peer and Adolescent Substance Usementioning
confidence: 99%